Combined APOGEE-GALAH stellar catalogues using the Cannon. Issue 1 (31st March 2022) - Nandakumar, Govind; Hayden, Michael R; Sharma, Sanjib; Buder, Sven; Asplund, Martin; Bland-Hawthorn, Joss; De Silva, Gayandhi M; D'Orazi, Valentina; Freeman, Ken C; Kos, Janez; Lewis, Geraint F; Martell, Sarah L; et al.
ABSTRACT: APOGEE and GALAH are two high resolution multi-object spectroscopic surveys that provide fundamental stellar parameters and multiple elemental abundance estimates for about half a million stars in the Milky Way. Both surveys observe in different wavelength regimes and use different data reduction pipelines leading to significant offsets and trends in stellar parameters and abundances for the common stars observed in both surveys. Such systematic differences/offsets in stellar parameters and abundances make it difficult to effectively utilize them to investigate Galactic abundance trends in spite of the unique advantage provided by their complementary sky coverage and different Milky Way components they observe. Hence, we use the Cannon data-driven method selecting a training set of 4418 common stars observed by both surveys. This enables the construction of two catalogues, one with the APOGEE-scaled and the other with the GALAH-scaled stellar parameters. Using repeat observations in APOGEE and GALAH, we find high precision in metallicity (∼0.02–0.4 dex) and alpha abundances (∼0.02–0.03 dex) for spectra with good signal-to-noise ratio (SNR > 80 for APOGEE and SNR > 40 for GALAH). We use open and globular clusters to validate our parameter estimates and find small scatter in metallicity (0.06 dex) and alpha abundances (0.03 dex) in APOGEE-scaled case. The final catalogues have been cross-matched with the Gaia EDR3 catalogue to enable their use to carry out detailed chemo-dynamic studies of the Milky Way from perspectives of APOGEE and GALAH.